2019
DOI: 10.1038/s41598-019-56605-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of mechanical lumpy skin disease virus transmission by Stomoxys calcitrans biting flies and Haematopota spp. horseflies

Abstract: Lumpy skin disease (LSD) is a devastating disease of cattle characterized by fever, nodules on the skin, lymphadenopathy and milk drop. Several haematophagous arthropod species like dipterans and ticks are suspected to play a role in the transmission of LSDV. Few conclusive data are however available on the importance of biting flies and horseflies as potential vectors in LSDV transmission. Therefore an in vivo transmission study was carried out to investigate possible LSDV transmission by Stomoxys calcitrans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 32 publications
9
129
0
Order By: Relevance
“…These data were then used to estimate the risk of transmission by these species with the aim of providing evidence with which to inform decisions during the implementation of measures to control LSDV. In our experimental model we observed that 37.5% of calves developed generalised LSD with the remaining 62.5% of calves classified as subclinical (no cutaneous nodules, positive qPCR in blood 27 ). This attack rate of 0.37 is comparable to other experimental models with field strains of LSDV (0.57 27 and 0.50 32 ).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…These data were then used to estimate the risk of transmission by these species with the aim of providing evidence with which to inform decisions during the implementation of measures to control LSDV. In our experimental model we observed that 37.5% of calves developed generalised LSD with the remaining 62.5% of calves classified as subclinical (no cutaneous nodules, positive qPCR in blood 27 ). This attack rate of 0.37 is comparable to other experimental models with field strains of LSDV (0.57 27 and 0.50 32 ).…”
Section: Discussionmentioning
confidence: 69%
“…This study describes a controlled experimental model of LSD that mimics disease features described in field outbreaks 2,4,8,11,12,37 and other experimental models 27,32 . Inoculated calves (both clinical and subclinical) were used to measure the acquisition (transmission from bovine to insect) and retention of LSDV by four potential vector species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations